The influence of current ratio (CR), debt to assets ratio (DAR), debt to equity ratio (DER), total assets turnover (TATO) on return on assets (ROA) in swarga farma pharmacies - Manasye Arveni Sinamo; Yoyo Sudaryo; Gurawan Dayona Ismail; Andre Suryaningprang; Dedi Supiyadi; Dadan Abdul Aziz (Sean Institute, 2024)
Return on Assets is one of the profitability ratios. Profitability is a financial ratio and one of the important indicators for measuring or assessing a company It can be used to analyze a company's finances because the level of profitability can describe the company's performance as seen from the company generating profits. This research aims to determine the effect of the Current Ratio (CR), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) on Return On Assets (ROA) at the Swarga Farma Pharmacy for the February – November Period. 2023. This research uses quantitative methods with descriptive and verification approaches. The data source used is secondary data, and data collection uses documentation studies in the form of annual financial reports. The sample used was a purposive sampling method. The data analysis techniques used are descriptive, regression, correlation, coefficient of determination, and partial or simultaneous hypothesis testing using the SPSS version 25 application. The results of this research show that. The results of the partial coefficient of determination show that CR makes a contribution that is not large enough and does not have a significant effect on ROA, DAR makes a contribution that is not large enough and does not have a significant effect on ROA, DER makes a contribution that is not large enough and does not have a significant effect. On ROA and TATO makes a fairly large contribution and does not significantly affect ROA. significant effect on ROA. Simultaneously, CR, DAR, DER, and TATO significantly affect ROA.